Desenvolvimento de biocatalisadores utilizando lipases de Rhizomucor mihei (RML) imobilizada em suporte de quitosana e sua aplicação na síntese de ésteres butirato de metila e butirato de etila - Oliveira, Ulisses Marcondes Freire de (2012)
Lipases (glycerol ester hydrolases, EC3.1.1.3) are versatile catalysts with broad and diverse possibilities of industrial applications. Its main application is essentially catalyze the hydrolysis of triglycerides. However, in micro-aqueous environments these enzymes have the ability to catalyze the reverse reaction of esterification. These enzymes do not require cofactors, have relatively low cost, are regioespecific, enantioselectives and may act on a broad range of temperature and pH. This work aimed to develop alternative technologies using enzymatic routes mediated by lipase from Rhizomucor miehei (RmL) immobilized on chitosan support in the presence of some classes of surfactants for the production of methyl butyrate and ethyl butyrate, two esters widely used in cosmetic and food industries. In this study two immobilization strategies were evaluated. In the first, the enzymes were immobilized in the presence of selected surfactants on chitosan supports previously activated with glutaraldehyde. In the second immobilization strategy, chitosan was crosslinked with glutaraldehyde after prior adsorption of the enzymes in the presence of surfactants. Among the immobilization procedures studied, the best results were achived when the enzyme was immobilized onto chitosan support in the presence of the surfactant sodium dodecyl sulphate SDS (0.23% m v-1) for 1 h at 4 ° C and 220 rpm, followed by crosslinking with 0.6% glutaraldehyde (v v-1) for 1 h at 25 ° C. In esterification experiments conducted with the best derivative, a detailed study of the parameters that affect the reaction rates were performed. The best yields were obtained when the reactions were conducted at 25 ° C, 6h and 150 rpm using n-heptane as a solvent. For methyl butyrate maximum esterification yield was 89% and for ethyl butyrate the maximum conversion observed was 92%. The results were comparable to yields observed when the esterification reactions were carried out with the commercial enzyme Lipozyme® and the soluble enzyme under the same reaction conditions.